Efficient red fluorescent OLEDs based on aggregation-induced emission combined with hybridized local and charge transfer state. (January 2021) - Yu, Yuan; Cang, Miao; Cui, Wei; Xu, Lei; Wang, Runze; Sun, Mizhen; Zhou, Huayi; Yang, Wenjun; Xue, Shanfeng
Abstract: Limited by the energy gap law and large conjugate structures, red organic light-emitting diodes (OLEDs) have long been criticized for their efficiency problems. The aggregation-induced emission (AIE) effect and the reverse intersystem crossing process can lead to high photoluminescent quantum yields (PLQYs) and high exciton utilization efficiency (EUE), two key objectives for obtaining efficient OLEDs. In this work, we chose benzothiadiazole as the acceptor (A) and triphenylamine and phenothiazine as the donors (Ds) to design and synthesize a D–A–D red fluorescent molecule, PBTPA. Results of systematic photophysical measurements indicated PBTPA to exhibit AIE trending, manifesting as aggregation-induced enhanced emission and the characteristics of hybridized local and charge transfer (HLCT) states. These features facilitated high solid-state luminescence efficiency and high exciton utilization to be achieved. A non-doped device fabricated using PBTPA displayed a red electroluminescence peak at 656 nm, corresponding to the Commission International de L'Eclairage coordinates of (0.65, 0.32), and an external quantum efficiency of 1.62%. By calculation, the EUE reached a value of 50%. According to the results of theoretical calculations, the effective hot exciton channel between the second triplet (T2 ) and the lowest singlet (S1 ) was responsible for the high EUE. This EUE value is relatively good for this type of red OLEDs. Evidence indicates that combining AIE and HLCT has excellent potential to aid the discovery of new-generation highly efficient red OLEDs. Graphical abstract: Image 1 Highlights: A novel D–A–D-type red fluorescent emitter, PBTPA, was designed and synthesized. It displayed aggregation-induced emission and hybridized local and charge transfer. Non-doped OLED had 50% EUE, efficient hot exciton channel, low-efficiency roll-off.